دور أخلاقيات الأعمال في تعزيز الانتماء التنظيمي "دراسة حالة شركة يمن موبايل للهاتف النقال" - القويي ماجد عبد الله; العلفي نبيل محمد (Journal of Amran University, 2024)
This study aimed to identify the role of business ethics in promoting organizational affiliation in Yemen Mobile Company - Case Study. To achieve the study's objectives, this study used the descriptive analytical method and depended on questionnaire as main tool for collecting data and information of this study. The sample of the study was random (228). After analyzing The data using the statistical analysis program (spss ) The results indicate that there is a positive correlation between the dimensions the business ethics (individual ethics, leadership ethics, organization ethics ) on promoting organizational affiliation, The results of the simple regression analysis indicated There is an impact of business ethics (individual ethics, leadership ethics, organization ethics ) on promoting organizational affiliation in Yemen Mobile Company, which means any increase in business ethics by one unit increases promoting organizational affiliation by (0. 514).